A composite voltage stability index for integrated energy systems based on L-index and the minimum eigenvalue of reduced Jacobian matrix. (October 2022) - Tang, W.H.; Li, W.W.; Zheng, J.H.; Wu, C.Q.; Wang, L.X.; Wei, Q.L.; Wu, Q.H.
Abstract: The closer interdependency of subsystems in integrated energy systems (IESs) and the continuous increase of electricity/gas/heat loads have brought great challenges to the stable operation of IESs. In response to the static voltage stability problem of IESs, this paper proposes a composite voltage stability index (CVSI) based on the minimum eigenvalue of a reduced Jacobian matrix and the known L-index. First, a unified multi-energy flow model for integrated electrical, natural gas and heating system is established, which comprises the steady-state modeling of each energy subsystem and coupling components in IESs. Then, an integrated multi-energy flow calculation method based on the Newton–Raphson algorithm is developed to solve the unified steady-state model of IESs. On the basis, the unified Jacobian matrix after multi-energy flow convergence can be obtained. Moreover, a reduced Jacobian matrix considering the impacts of multi-energy state variables on the reactive power of electrical power system (EPS) is constructed. Afterward, the CVSI is proposed, which combines the minimum eigenvalue of the constructed reduced Jacobian matrix and the L-index derived from bus voltage calculation formula. The proposed CVSI takes both the voltage stability margin of whole system and the voltage stability of electrical buses into consideration. Finally, numerical simulations are exploited to verify the effectiveness and applicability of the proposed voltage stability index. Highlights: A unified multi-energy flow model is established for integrated energy systems. A reduced Jacobian matrix is constructed based on the unified multi-energy flow model. The composite voltage stability index is proposed for static voltage stability analysis of integrated energy systems. The static voltage stability analysis based on the proposed voltage stability index is investigated on two test systems.